Environmental Ethics in the Hadith: Building Ecological Awareness in the Era of Global Warming - Amir, Sulaiman Muhammad; Julaiha P, Juli; Hasabalh, Hashim Mohammed Adam; Harahap, Alwi Padly (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2025)
Global warming has become a pressing issue that impacts the sustainability of life on Earth. This environmental crisis raises questions about how Islamic ethical values, especially those derived from the hadith, can play a role in building ecological awareness in modern society. The hadith as one of the main sources of Islamic teachings contains moral principles that can be interpreted in an environmental context, such as preserving nature, preventing damage, and treating living things fairly. This study aims to explore the ecological ethics contained in the hadith and its relevance to the issue of global warming. Using a descriptive-analytical qualitative method, this study analyzes the hadiths related to human responsibility towards nature and relates them to the concept of modern ecology. The study’s results indicate that the values of environmental ethics in the hadith provide a strong theological basis for Muslims to be actively involved in maintaining the balance of the ecosystem and reducing the impact of global warming. The main conclusion of this study is that Islamic teachings, through understanding the hadith, can make a significant contribution to building ecological awareness and real action in facing the global environmental crisis.